Recrudescence of Plasmodium malariae after Quinine - Irfanali R. Kugasia; Farhana K. Polara; Hussein Assallum (Case Reports in Medicine)
Plasmodium malariae causes uncommon benign malaria found in the malaria endemic regions mostly of Sub-Saharan Africa. As Plasmodium malariae does not have a continued liver stage in humans the only way to have reinfection without reexposure is through recrudescence. However, reports of its recrudescence after antimalarials are rare with only a handful of case reports in the literature. Research in this field to date has not been able to establish definitively an emergence of resistance in Plasmodium malariae to commonly used antimalarials. In the presented case, patient had a recrudescence of P. malariae after full treatment with quinine and clindamycin. This recrudescence was treated with full course of chloroquine with clearance of parasite from blood immediately after treatment and at two months’ follow up. The recrudescence in this case cannot be explained by mechanisms explained in prior articles. We propose that the indolence of some of the Plasmodium malariae trophozoites in the blood can shield them from the effect of the toxic effects of antimalarials and enable them to produce recrudescence later. However, when recrudescence happens, this should not be considered a case of development of resistance and a course of chloroquine should be considered.